The mediating effects of gratitude and self-compassion on college students during the COVID-19 pandemic - Leslie Ramos Salazar; Audrey Meador (Humanities & Social Sciences Communications)
Abstract College students experienced academic hardships while completing online courses during the COVID-19 pandemic. As such, there is a need to investigate the generation status, computer-mediated communication competence (CMC), and active learning of college students. This study focused on examining the generation differences of students in relation to their active learning, self-compassion, and gratitude. This study also examined gratitude and self-compassion as mediators of the relationship between CMC and active learning. A cross-sectional, convenience sample of 429 college students was obtained from a public institution. Findings demonstrated that first-generation students reported higher self-compassion and active learning than other generations students. Additionally, missing graded assignments had a significant effect on first-generation students’ CMC, and CMC positively predicted their active learning. Further, gratitude and self-compassion mediated the positive relationship between CMC and active learning. Recommendations and implications are also offered to stakeholders in higher education.